A Review on the Role of Poultry in Food Borne Salmonellosis and Its Public Health Importance - Manoj, Jinu; Singh, M. K. (Research Aspects in Agriculture and Veterinary Science Vol. 1, 2021)
Salmonella organisms cause foodborne disease outbreaks having significant public health concern. Salmonella is more frequently isolated from poultry species than from other livestock animals. All the fractions of poultry production can be affected by Salmonella organisms like hatchery, incubators, breeding facilities, commercial raising operations of layers and broilers, feed preparation units and factories, transportation systems, commercialization facilities and slaughterhouses. Globalization makes it possible for a contaminated foodstuff to affect the health of people in several countries at the same time. Several cases of foodborne salmonellosis originated from poultry products have been reported globally including India. The predominant serovars of Salmonella, having public health importance are mainly S. enteritidis and S. typhimurium. Antibiotic resistant serotypes of poultry origin are alarmingly increasing. Poultry food safety is a function of multiple risk factors. For effective prevention and control of foodborne salmonellosis, there should be programmes for creating awareness among consumers about the food safety and guiding the food handlers and animal breeders mainly of poultry, regarding safe production of food starting from farm to the table.